The Rôle of Memory in two "fictions de l'identitaire" from Quebec:: Sergio Kokis's Le Pavillon des miroirs and Jean-François Chassay's Les Ponts - Vautier, Marie (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 1999)
Numerous contemporary Québécois fictions show a willingness to engage in necessarily non-solidly-defined memories, to accept the nebulous quality of these memories, and to revel in this dynamic praxis. Sergio Kokis, in Le Pavillon des miroirs, investigates the notion of identity through memory. Instead of resolving his identity issues through involvement with the community, Kokis's narrator uses his paintings to connect his memories to l'identitaire. In Jean-Francois Chassay's Les Ponts, unstable and unverifiable memories have replaced history in the process of creating l'indentitaire. Through their explorations of memory and l'identitaire, these two Québécois novels constitute examples of a postcolonial exploration of identity as process and memory as mouvance.